Calcium Channel Blockers - Elliott, William J. (J Clin Hypertens (Greenwich), 2011)
J Clin Hypertens (Greenwich). 2011;13:687–689. ©2011 Wiley Periodicals, Inc. KEY POINTS AND PRACTICAL RECOMMENDATIONS: •  Calcium channel blockers, which dilate arteries by reducing calcium flux into cells, effectively lower blood pressure, especially in combination with other drugs, and some formulations of agents of this class are approved for treating angina or cardiac dysrhythmias. •  Calcium channel blockers reduce blood pressure across all patient groups, regardless of sex, race/ethnicity, age, and dietary sodium intake. •  Nondihydropyridine calcium channel blockers are more negatively chronotropic and inotropic than the dihydropyridine subclass, which is important for patients with cardiac dysrhythmias or who need β‐blockers. •  Extensive experience in comparative randomized trials indicates that an initial calcium antagonist can prevent all major types of cardiovascular disease, except heart failure (for which a diuretic is superior). Initial dihydropyridine calcium channel blockers have not reduced the rate of progression of renal disease as well as inhibitors of the renin‐angiotensin system, although members of the nondihydropyridine subclass can reduce albuminuria. •  High doses of dihydropyridine calcium channel blockers often cause edema, headache, flushing and tachycardia; high doses of verapamil can cause constipation. Diltiazem and verapamil have important drug interaction with digoxin and cyclosporine, among others.